2020
DOI: 10.1002/acn3.51217
|View full text |Cite
|
Sign up to set email alerts
|

Vocal music enhances memory and language recovery after stroke: pooled results from two RCTs

Abstract: Objective: Previous studies suggest that daily music listening can aid stroke recovery, but little is known about the stimulus-dependent and neural mechanisms driving this effect. Building on neuroimaging evidence that vocal music engages extensive and bilateral networks in the brain, we sought to determine if it would be more effective for enhancing cognitive and language recovery and neuroplasticity than instrumental music or speech after stroke. Methods: Using data pooled from two single-blind randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 49 publications
7
53
0
3
Order By: Relevance
“…Furthermore, as previous studies indicate that some types of musical activities are more beneficial to wellbeing than others 78,79 , future research should focus on highlighting the particular musical activities that are associated with better mental health. Nevertheless, since we did not find consistent relationships with reduction in anxiety or depression associated with other activities besides food-related ones, we infer that perhaps music should be encouraged as a potential coping strategy, particularly given its relative accessibility and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as previous studies indicate that some types of musical activities are more beneficial to wellbeing than others 78,79 , future research should focus on highlighting the particular musical activities that are associated with better mental health. Nevertheless, since we did not find consistent relationships with reduction in anxiety or depression associated with other activities besides food-related ones, we infer that perhaps music should be encouraged as a potential coping strategy, particularly given its relative accessibility and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, Wilkins and others showed that the default mode network (especially precuneus) was more connected when listening to preferred music than when listening to music with less emotional meaning [ 29 ]. The health benefits of favorite music listening were originally shown by Särkämö and others who reported faster emotional and cognitive recovery in acute stroke patients who were instructed to listen to their favorite music, when compared with audio book listening or a passive control group [ 30 ] (for replication and upgrade, see [ 31 ]).…”
Section: Discussionmentioning
confidence: 99%
“…These include active interventions that utilize instrument playing or musical rhythm to rehabilitate deficits in motor control of movements (hemiparesis) [ 13 ] and singing-based methods to rehabilitate deficits in speech production (aphasia) [ 14 ] as well as receptive interventions that utilize music listening. In three randomized controlled trials (RCTs), daily music listening during the first three post-stroke months has been reported to enhance the recovery of verbal memory, attention, and language skills compared to a control intervention (audiobook listening) or standard care [ 15 , 16 , 17 ]. Using structural and functional magnetic resonance imaging (s/fMRI), these positive behavioural effects have been coupled with structural neuroplasticity in prefrontal, temporal, and limbic brain regions and white matter tracts [ 17 , 18 , 19 ], as well as with increased functional activation or connectivity in motor cortical, temporal, and parietal regions [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In three randomized controlled trials (RCTs), daily music listening during the first three post-stroke months has been reported to enhance the recovery of verbal memory, attention, and language skills compared to a control intervention (audiobook listening) or standard care [ 15 , 16 , 17 ]. Using structural and functional magnetic resonance imaging (s/fMRI), these positive behavioural effects have been coupled with structural neuroplasticity in prefrontal, temporal, and limbic brain regions and white matter tracts [ 17 , 18 , 19 ], as well as with increased functional activation or connectivity in motor cortical, temporal, and parietal regions [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation